1996
DOI: 10.1021/ed073p99
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase NMR Study of the DCl-HBr Isotope Exchange Reaction

Abstract: A physical chemistry laboratory experiment is described in which proton and deuteron FT-NMR spectra are used to determine the equilibrium constant for the isotope exchange reaction DCl + HBr <==> DBr + HCl . The measurement illustrates an unusual gas phase application of NMR spectroscopy. The results are in good accord with a 297K value of Kp = 0.818, calculated from statistical thermodynamics using vibrational-rotational constants. The latter can be taken from the literature or can be conveniently determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite its wide use for the analysis of liquid-phase mixtures, NMR spectroscopy has been used to analyze gas-phase mixtures in only a few cases. Of those, only one study tested the accuracy of the method with a well-defined gas mixture, and that study was also the only one that reported measurement uncertainties for the NMR analysis. In that work, a gravimetrically prepared, 10-component natural gas surrogate (with light hydrocarbons ranging from methane to hexane, as well as CO 2 ) was analyzed.…”
mentioning
confidence: 99%
“…Despite its wide use for the analysis of liquid-phase mixtures, NMR spectroscopy has been used to analyze gas-phase mixtures in only a few cases. Of those, only one study tested the accuracy of the method with a well-defined gas mixture, and that study was also the only one that reported measurement uncertainties for the NMR analysis. In that work, a gravimetrically prepared, 10-component natural gas surrogate (with light hydrocarbons ranging from methane to hexane, as well as CO 2 ) was analyzed.…”
mentioning
confidence: 99%